Variability of dental abnormalities according to the timing of anticancer therapy: A report of two cases. Issue 2 (August 2022) - Kim, Gimin; Lee, Jaesik
Abstract: Background: Current multimodality therapies have increased the survival of patients with childhood cancer. However, these therapies increase the risk of dental complications. Case report: The first case was a 7-year-old girl who was diagnosed with leukemia at around 8 months of age and received anticancer therapy for about 1 year. The second case was an 8-year-old boy who was diagnosed with leukemia at around the age of 6 and received anticancer therapy for about 2 years. Based on long-term follow-up of two cases, tooth agenesis and microdontia occurs when anticancer therapy is performed at the initial stage of tooth development. However shortening roots of the affected teeth can be found when it is performed at the late stage of tooth development. Conclusions: Early diagnosis and understanding of dental developmental defects resulting from anticancer therapy are essential for preventing tooth loss and space-related problems in the oral cavity.